2020
DOI: 10.1177/2158244020902090
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome in Chilean Midwifery Students

Abstract: The student Burnout Syndrome is a response to chronic and severe stress linked to the role of the students and their academic context. This study aims at determining the prevalence and severity of the student Burnout Syndrome on a sample of midwifery students and its associated factors. The study is observational, cross-sectional, and analytical, with a sample of 140 students of a Chilean university. The study variables were as follows: sociodemographic background, academic profile, student Burnout Syndrome sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
2
5
0
3
Order By: Relevance
“…It is already known that the academic stressors are related to stress, anxiety, depression, and when combined with extra load on studying as well as the need to enhance performance and concentration, students may resort to the use of antidepressants to avoid episodes of social anxiety and depressive behaviour. This finding is consistent with other studies, that reported students who use antidepressants, present high levels of burnout [47][48][49] . The misuse of alcohol and/or other substances are linked with burnout, and by neglecting that, it can lead to serious consequences.…”
Section: Discussionsupporting
confidence: 93%
“…It is already known that the academic stressors are related to stress, anxiety, depression, and when combined with extra load on studying as well as the need to enhance performance and concentration, students may resort to the use of antidepressants to avoid episodes of social anxiety and depressive behaviour. This finding is consistent with other studies, that reported students who use antidepressants, present high levels of burnout [47][48][49] . The misuse of alcohol and/or other substances are linked with burnout, and by neglecting that, it can lead to serious consequences.…”
Section: Discussionsupporting
confidence: 93%
“…It is a response to chronic and intense stress connected to students’ roles and the situational context in which they function. It has been proven that different leisure activities can protect against professional burnout [ 9 ]. The achievement domain demonstrates whether midwifery students are able to react proactively in task-oriented situations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, midwifery education and the profession of a midwife require discussions regarding the complexity of the behaviors displayed by young people in certain situations. The requirements imposed on midwifery students concern mainly their education, work life, and leisure time activities [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…En Chile durante el año 2020 midieron al SB en estudiantes de la carrera de obstetricia que cursaban el 3er año y 4to año, en ambos casos se obtuvo que la mayoría de los estudiantes de 3er año obtuvieron un 72,1% de nivel moderado y el 4to año de estudiantes con un 47.5% de nivel moderado 11 .…”
Section: Planteamiento Del Problemaunclassified
“…Rendimiento en el examen parcial de los estudiantes con SB alto (X, RIQ) 15 (5,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Rendimiento en el examen parcial de los estudiantes con SB muy alto (X, RIQ)…”
Section: *Prueba Kruskal Wallisunclassified